A global perspective on newborn congenital hypothyroidism screening - Kopel, Jonathan (Proc (Bayl Univ Med Cent), 2019)
Congenital hypothyroidism (CH) is a thyroid hormone deficiency syndrome in newborns resulting from incomplete thyroid development and decreased thyroid hormone biosynthesis or thyroid-stimulating hormone secretion. Without early treatment, newborns with CH have irreversible neurological deficits and long-term metabolic complications. Therefore, several countries have implemented widespread newborn screening to identify and treat CH in newborns. Although newborn screening has improved diagnosis and treatment outcomes for CH, several questions remain concerning the etiology and increased incidence of CH in different populations. Moreover, the increase in the number of preterm, low-birth-weight newborns and of newborns admitted to the neonatal intensive care unit presenting with CH requires additional research to detect and treat all forms of CH.